Menelusuri Jejak Nilai Iman Kristen dalam Kepemimpinan Tallu Lalikan di Lembang Limbong Sangpolo - Devisa, Orin; Sumule, Linus (IAKN TORAJA, 2023)
Abstract: Community life is strongly influenced by the order and values ​​prevailing in that society. The value itself is the biggest contribution to the growth and development of society. In Lembang, Sangpolo uses Tallu Lalikan. Tallu Lalikan itself is a stone kitchen stove, numbering three. Tallu Lalikan in this context is not about religious views but rather on the organizational structure of society, namely Religion or Aluk, Adat or ada' and Government. The role of Tallu Lalikan itself is how the collaboration of Christian faith and community growth is played by certain figures. In this study, a qualitative approach was used with library research and field research data collection techniques, namely data observation and interviews. The aim of this research is to find out the traces of the value of the Christian Faith in the Tallu Lalikan leadership in Lembang Limbong Sangpolo. Through this research it is hoped that it will provide results regarding the positive influence of the value of the Christian faith in leadership on the life order of the Tallu Lalikan Community in Lembang Limbong Sangpolo. Tallu Lalikan leadership will build good relationships and will produce quality social life. Keywords: Christian faith, Leadership, Governance and Tallu Lalikan This work is licensed under a Creative Commons Attribution- -ShareAlike 4.0 International (CC BY-SA 4.0) Abstrak: Kehidupan bermasyarakat sangat dipengaruhi oleh tatanan dan nilai-nilai yang berlaku dalam Masyarakat tersebut. Nilai itu sendiri yang menjadi sumbangsi terbesar dalam pertumbuhan dan perkembangan Masyarakat. Di Lembang Sangpolo diterapkan Tallu Lalikan. Tallu Lalikan itu sendiri adalah batu tungku dapur yang berjumlah tiga buah. Tallu Lalikan dalam konteks ini bukanlah mengenai pandangan religius tetapi lebih kepada tatanan organisasi Masyarakat, yaitu Agama atau Aluk, Adat atau ada’ dan Pemerintahan. Peranan dari Tallu Lalikan sendiri adalah bagaimana Kolaborasi iman Kristen dan pertumbuhan Masyarakat yang diperankan oleh tokoh-tokoh tertentu. Dalam penelitian ini mengunakan pendekatan Kualitatif dengan teknik pengumpulan data Library research dan field research yaitu data observasi dan wawancara. Dari penelitian ini memiliki tujuan yakni mengetahui jejak nilai Iman Kristen dalam kepemimpinan Tallu Lalikan di Lembang Limbong Sangpolo. Hasil dari penelitian berdasarkan obvervasi dan wawancara, pemimpin dari tiga unsur tersebut, memiliki hati seperti hamba, integritas, spiritual iman kristen dan bertanggung jawab. Kepemimpinan Tallu Lalikan akan membangun relasi yang baik dan akan menghasilkan kehidupan bermasyarakat yang berkualitas. Kata Kunci: Iman Kristen, kepemimpinan, pemerintahan dan tallu lalikan